Composite solid electrolyte containing modified molecular sieve and preparation and application thereof
By using hydrophobically modified molecular sieve in solid electrolytes, the problems of channel blockage and side reactions caused by the high adsorption of the molecular sieve to moisture are solved, and better electrochemical stability and cyclic stability are achieved.
Patent Information
- Application Number
- CN202411772005.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
AI Technical Summary
The solid electrolyte containing molecular sieves in the prior art can easily lead to pore blockage and side reactions due to its high adsorption of moisture, which affects the electrochemical stability.
The hydrophobic modified molecular sieve is used to form a hydrophobic layer on the surface of the molecular sieve to reduce the adsorption capacity to moisture, thereby reducing the risk of channel blockage and side reactions.
It improves the electrochemical stability of the composite solid electrolyte, enhances the tolerance to moisture and oxygen in the air, and extends the cycling stability of the solid battery.
Smart Images

Figure CN119627206A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries and relates to a composite solid electrolyte comprising a modified molecular sieve, and in particular to a composite solid electrolyte comprising a modified molecular sieve and a preparation method and application thereof. Background Art
[0002] With the vigorous development of the new energy vehicle field, the demand for high energy density and high power density batteries has also increased. Lithium-ion batteries have the advantages of high energy density, high operating voltage, high capacity and small size, which makes them widely used. However, the traditional liquid organic electrolyte system is toxic, flammable and prone to short circuit and leakage, which can lead to safety accidents such as combustion and explosion, and has great safety hazards.
[0003] In order to solve the problems existing in the liquid organic electrolyte system, the development of solid electrolytes is imperative. Solid electrolytes not only have high safety and high energy density, but also have high strength and high density, which is conducive to inhibiting the formation of lithium dendrites and avoiding the short circuit problem caused by lithium dendrites.
[0004] Molecular sieve is a naturally occurring microporous material with unique inorganic properties. It has high thermal stability and mechanical strength. It can also build lithium ion transmission channels in electrolytes. Molecular sieve has broad application prospects in solid electrolytes. However, due to the high adsorption of molecular sieves to water, the electrolyte membrane prepared by them is very sensitive to moisture in the air, which can easily cause pore blockage and side reactions.
[0005] CN112864456A discloses a molecular sieve-based solid electrolyte and a preparation method, and an integrated solid electrolyte-electrode material. The molecular sieve-based solid electrolyte includes a molecular sieve membrane or a molecular sieve sheet; there are movable cations in the molecular sieve pores. However, the molecular sieve membrane or molecular sieve sheet in the molecular sieve-based solid electrolyte disclosed therein has a high adsorption capacity for water, and is prone to pore blockage and side reactions.
[0006] CN117039129A discloses a modified molecular sieve-based solid electrolyte and its preparation method and application. The reference provides a modified molecular sieve-based solid electrolyte, including a molecular sieve-based solid electrolyte and a modifying substance dispersed in the pore structure of the molecular sieve-based solid electrolyte; the modifying substance can produce a coordination effect with the carriers in the molecular sieve-based solid electrolyte; the modifying substance contains one or more of nitrogen, oxygen, and sulfur elements. The modified molecular sieve-based solid electrolyte can well meet the requirements of assembling all-solid-state batteries, so that the electrochemical performance of the all-solid-state battery exceeds the electrochemical performance of energy storage devices based on liquid electrolytes. Similarly, the molecular sieve in the modified molecular sieve-based solid electrolyte disclosed therein has strong water absorption, which is not conducive to the performance of the solid electrolyte.
[0007] The solid electrolytes containing molecular sieves disclosed in the prior art all have certain defects. There are problems such as blockage of the pores of the solid electrolyte and occurrence of side reactions due to the high adsorption of water by the molecular sieves. Therefore, it is very important to develop and design a new type of composite solid electrolyte containing modified molecular sieves and its preparation and application. Summary of the invention
[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide a composite solid electrolyte comprising a modified molecular sieve, and preparation and application thereof. The modified molecular sieve in the composite solid electrolyte provided by the present invention is a hydrophobically modified molecular sieve. The hydrophobic layer covered by the molecular sieve reduces the adsorption capacity of the molecular sieve to moisture, reduces the sensitivity of the composite solid electrolyte comprising the modified molecular sieve to moisture in the air, reduces the risk of pore blockage and side reactions in the composite solid electrolyte, thereby making the composite solid electrolyte have better electrochemical stability.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a composite solid electrolyte comprising a modified molecular sieve, wherein the modified molecular sieve in the composite solid electrolyte is a hydrophobically modified molecular sieve, and the hydrophobically modified molecular sieve comprises a molecular sieve and a hydrophobic layer covering the surface of the molecular sieve.
[0011] The modified molecular sieve in the composite solid electrolyte provided by the present invention is a hydrophobically modified molecular sieve. The hydrophobic layer covered by the molecular sieve reduces the molecular sieve's ability to adsorb moisture, reduces the sensitivity of the composite solid electrolyte containing the modified molecular sieve to moisture in the air, and reduces the risk of pore blockage and side reactions in the composite solid electrolyte, thereby making the composite solid electrolyte have better electrochemical stability.
[0012] Preferably, the hydrophobically modified molecular sieve comprises any one of a hydrophobically modified MCM-22 molecular sieve, a hydrophobically modified TS-1 molecular sieve, a hydrophobically modified ZSM-5 molecular sieve, a hydrophobically modified X molecular sieve or a hydrophobically modified Y molecular sieve, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of a hydrophobically modified MCM-22 molecular sieve and a hydrophobically modified TS-1 molecular sieve, a combination of a hydrophobically modified ZSM-5 molecular sieve and a hydrophobically modified X molecular sieve, a combination of a hydrophobically modified X molecular sieve and a hydrophobically modified Y molecular sieve, or a combination of a hydrophobically modified MCM-22 molecular sieve, a hydrophobically modified TS-1 molecular sieve and a hydrophobically modified ZSM-5 molecular sieve.
[0013] Preferably, the composite solid electrolyte further comprises a solid electrolyte and a lithium salt, wherein the solid electrolyte comprises PVDF-HFP, and the molecular weight of the PVDF-HFP is 4×10 5 ~5×10 5 , for example, it can be 4×10 5 4.1×10 5 4.2×10 5 , 4.3×10 5 , 4.4×10 5 , 4.5×10 5 , 4.6×10 5 , 4.7×10 5 , 4.8×10 5 , 4.9×10 5 or 5×10 5 , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] The solid electrolyte in the present invention is preferably PVDF-HFP (poly(vinylidene fluoride-co-hexafluoropropylene)). PVDF-HFP has excellent oxidation resistance and stability to lithium, and its use in solid-state batteries is beneficial to further enhance the stability of solid-state batteries.
[0015] The molecular weight of PVDF-HFP in the present invention is 4×10 5 ~5×10 5 When the molecular weight of PVDF-HFP is within this range, PVDF-HFP can provide sufficient mechanical strength and flexibility while maintaining high ionic conductivity. In addition, PVDF-HFP with a molecular weight within this range helps to improve the thermal stability of the electrolyte, which is crucial to improving the safety and cycle stability of solid-state batteries.
[0016] Preferably, the lithium salt includes any one of LiTFSI, LiBF4 or LiClO4 or a combination of at least two thereof. Typical but non-limiting combinations include a combination of LiTFSI and LiBF4, a combination of LiBF4 and LiClO4, or a combination of LiTFSI, LiBF4 and LiClO4.
[0017] In a second aspect, the present invention provides a method for preparing the composite solid electrolyte according to the first aspect, the preparation method comprising:
[0018] The molecular sieve is hydrophobically modified to form a hydrophobic layer on the surface of the molecular sieve to obtain a hydrophobically modified molecular sieve; and the obtained hydrophobically modified molecular sieve is used as a raw material to prepare a composite solid electrolyte.
[0019] The structure of the hydrophobically modified molecular sieve obtained after the molecular sieve is hydrophobically modified in the preparation method provided by the present invention does not change. The modification method is simple and environmentally friendly, and the raw materials can be reused, which is suitable for large-scale industrial production. In addition, the composite solid electrolyte prepared with the hydrophobically modified molecular sieve can greatly reduce the adsorption and reaction of moisture and oxygen in the air during the preparation of solid-state batteries and the operation of solid-state batteries, thereby making the solid-state batteries have excellent cycle stability.
[0020] Preferably, the preparation method further comprises calcination activation before the hydrophobic modification, and the calcination activation temperature is 300 to 600° C. and the time is 2 to 8 hours.
[0021] The calcination activation in the preparation method provided by the present invention can remove moisture and impurities adsorbed in the molecular sieve, thereby preventing the moisture and impurities from having an adverse effect on the performance of the hydrophobically modified molecular sieve.
[0022] The calcination activation temperature in the present invention is 300-600°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; preferably, it is 400-600°C.
[0023] The calcination activation time in the present invention is 2 to 8 hours, for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, the hydrophobic modification method comprises: mixing a molecular sieve, a silanization agent, a reaction solvent and a catalyst, and performing a silanization reaction to obtain a hydrophobically modified molecular sieve;
[0025] The solid-liquid ratio of the molecular sieve to the silanization agent in the mixture is 1:(0.1-5), the solid-liquid ratio of the molecular sieve to the reaction solvent is 1:(5-40), and the solid-liquid ratio of the molecular sieve to the catalyst is 1:(0.1-5), and the units of the solid-liquid ratios are all g / mL.
[0026] The purpose of the silanization reaction in the present invention is to form a hydrophobic layer on the surface of the molecular sieve through a chemical reaction to achieve a hydrophobic effect.
[0027] In the present invention, by limiting the solid-liquid ratio of the molecular sieve to the silanization agent to 1: (0.1-5), the solid-liquid ratio of the molecular sieve to the reaction solvent to 1: (5-40), and the solid-liquid ratio of the molecular sieve to the catalyst to 1: (0.1-5), it is beneficial to enhance the hydrophobic properties of the molecular sieve without affecting the structure of the molecular sieve, thereby improving the stability of the solid-state battery.
[0028] The solid-to-liquid ratio of the molecular sieve to the silanization agent in the mixture of the present invention is 1:(0.1-5), for example, it can be 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The unit of the solid-to-liquid ratio is g / mL.
[0029] The solid-liquid ratio of the molecular sieve to the reaction solvent in the mixture of the present invention is 1:(5-40), for example, it can be 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35 or 1:40, but is not limited to the listed values. Other unlisted values within the numerical range are also applicable. The unit of the solid-liquid ratio is g / mL.
[0030] The solid-to-liquid ratio of the molecular sieve to the catalyst in the mixture of the present invention is 1:(0.1-5), for example, it can be 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The unit of the solid-to-liquid ratio is g / mL.
[0031] Preferably, the mixing method includes magnetic stirring.
[0032] Preferably, the magnetic stirring has a rotation speed of 150 to 600 r / min, a temperature of 25 to 60° C., and a time of 2 to 48 h.
[0033] The rotation speed of the magnetic stirring in the present invention is 150-600r / min, for example, it can be 150r / min, 200r / min, 250r / min, 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min or 600r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] The temperature of the magnetic stirring in the present invention is 25-60°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] The magnetic stirring time in the present invention is 2 to 48 hours, for example, it can be 2h, 5h, 8h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h or 48h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the molecular sieve comprises any one of MCM-22 molecular sieve, TS-1 molecular sieve, ZSM-5 molecular sieve, X molecular sieve or Y molecular sieve, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of MCM-22 molecular sieve and TS-1 molecular sieve, a combination of ZSM-5 molecular sieve and X molecular sieve, a combination of X molecular sieve and Y molecular sieve, or a combination of MCM-22 molecular sieve, TS-1 molecular sieve and ZSM-5 molecular sieve.
[0037] Preferably, the silanization agent includes any one of chlorosilane, trimethylchlorosilane, hexamethyldisilane, dimethyldiethoxysilane, dodecyltrimethoxysilane or n-octyltriethoxysilane, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of chlorosilane and trimethylchlorosilane, a combination of hexamethyldisilane and dimethyldiethoxysilane, a combination of dimethyldiethoxysilane and dodecyltrimethoxysilane, a combination of dodecyltrimethoxysilane and n-octyltriethoxysilane, or a combination of hexamethyldisilane, dimethyldiethoxysilane and dodecyltrimethoxysilane.
[0038] Preferably, the reaction solvent comprises ethanol.
[0039] Preferably, the catalyst comprises any one of sodium hydroxide aqueous solution, ammonium carbonate aqueous solution or ammonia water, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of sodium hydroxide aqueous solution and ammonium carbonate aqueous solution, a combination of ammonium carbonate aqueous solution and ammonia water, or a combination of sodium hydroxide aqueous solution, ammonium carbonate aqueous solution and ammonia water.
[0040] In the present invention, any one of sodium hydroxide aqueous solution, ammonium carbonate aqueous solution or ammonia water or a combination of at least two of them is added as a catalyst during the silanization reaction, which promotes the hydrolysis reaction of the silanization agent itself and accelerates the reaction process.
[0041] Preferably, the hydrophobic modification further comprises washing and vacuum drying performed in sequence after the silanization reaction.
[0042] The purpose of washing in the present invention is to remove the unreacted silanization agent and other impurities on the surface of the molecular sieve, thereby preventing the silanization agent and other impurities from affecting the performance of the hydrophobically modified molecular sieve, thereby affecting the performance of the composite solid electrolyte.
[0043] Preferably, the washing reagent comprises ethanol.
[0044] Preferably, the washing is performed 3 to 5 times, for example, 3 times, 4 times or 5 times.
[0045] Preferably, the temperature of the vacuum drying after washing is 30 to 100° C. and the time is 1 to 24 hours.
[0046] The temperature of vacuum drying after washing in the present invention is 30-100°C, for example, it can be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] The time for vacuum drying after washing in the present invention is 1 to 24 hours, for example, it can be 1 hour, 3 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the method for preparing a composite solid electrolyte using the obtained hydrophobically modified molecular sieve as a raw material comprises:
[0049] The solid electrolyte, lithium salt, organic solvent and the obtained hydrophobically modified molecular sieve are mixed to obtain a mixed slurry, the obtained mixed slurry is cast into a shape, and then vacuum dried to obtain the composite solid electrolyte;
[0050] The mass ratio of the solid electrolyte, the lithium salt and the obtained hydrophobically modified molecular sieve in the mixture is (0.3-1.5):1:(0.05-1.5).
[0051] In the present invention, the mass ratio of the solid electrolyte, the lithium salt and the obtained hydrophobically modified molecular sieve is limited, thereby limiting the mass ratio of the solid electrolyte, the lithium salt and the obtained hydrophobically modified molecular sieve in the obtained solid-state battery, thereby ensuring the electrochemical performance of the solid-state battery and enhancing the stability of the solid-state battery.
[0052] The mass ratio of the solid electrolyte to the lithium salt in the mixture of the present invention is (0.3-1.5):1, for example, it can be 0.3:1, 0.5:1, 0.7:1, 0.9:1, 1.1:1, 1.3:1 or 1.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] The mass ratio of the lithium salt to the obtained hydrophobically modified molecular sieve in the mixture of the present invention is 1:(0.05-1.5), for example, it can be 1:0.05, 1:0.1, 1:0.3, 1:0.5, 1:0.7, 1:0.9, 1:1.1, 1:1.3 or 1:1.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the mass ratio of lithium salt to organic solvent in the mixture is 1:(2-12), for example, 1:2, 1:4, 1:6, 1:8, 1:10, 1:12, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] Preferably, the organic solvent comprises any one of N-methylpyrrolidone (NMP), anhydrous acetonitrile, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) or tetrahydrofuran, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of N-methylpyrrolidone and anhydrous acetonitrile, a combination of N,N-dimethylformamide and dimethyl sulfoxide, a combination of dimethyl sulfoxide and tetrahydrofuran, or a combination of N,N-dimethylformamide, dimethyl sulfoxide and tetrahydrofuran.
[0056] Preferably, the casting forming includes injecting the obtained mixed slurry into a mold for molding.
[0057] Preferably, the vacuum drying after casting is carried out at a temperature of 60 to 120° C. and a time of 8 to 24 hours.
[0058] The temperature of vacuum drying after casting and forming in the present invention is 60-120°C, for example, it can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] The vacuum drying time after casting in the present invention is 8 to 24 hours, for example, it can be 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:
[0061] (1) calcining and activating the molecular sieve at 300-600° C. for 2-8 hours to obtain an activated molecular sieve;
[0062] (2) mixing the activated molecular sieve obtained in step (1), a silanization agent, a reaction solvent and a catalyst having a solute mass concentration of 5 to 40 wt % by magnetic stirring at a speed of 150 to 600 r / min, a temperature of 25 to 60° C., and a time of 2 to 48 h, performing a silanization reaction, and then washing with ethanol 3 to 5 times and vacuum drying at 30 to 100° C. for 1 to 24 h to obtain a hydrophobically modified molecular sieve;
[0063] The solid-liquid ratio of the activated molecular sieve to the silanization agent in the mixture is 1:(0.1-5), the solid-liquid ratio of the activated molecular sieve to the reaction solvent is 1:(5-40), and the solid-liquid ratio of the activated molecular sieve to the catalyst is 1:(0.1-5), and the units of the solid-liquid ratios are all g / mL;
[0064] (3) A solid electrolyte, a lithium salt, an organic solvent and the hydrophobically modified molecular sieve obtained in step (2) are mixed to obtain a mixed slurry, wherein the mass ratio of the solid electrolyte, the lithium salt and the hydrophobically modified molecular sieve in the mixture is (0.3-1.5):1:(0.05-1.5), and the mass ratio of the lithium salt to the organic solvent is 1:(2-12). The obtained mixed slurry is injected into a mold for molding, and then vacuum dried at 60-120° C. for 8-24 hours to obtain the composite solid electrolyte.
[0065] In a third aspect, the present invention provides a solid-state battery, comprising the composite solid-state electrolyte described in the first aspect.
[0066] The solid-state battery provided in the present invention includes the composite solid-state electrolyte. Since the solid-state electrolyte has high stability, the solid-state battery including the composite solid-state electrolyte exhibits excellent stability.
[0067] In a fourth aspect, the present invention provides a vehicle, comprising the solid-state battery described in the third aspect.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] (1) The modified molecular sieve in the composite solid electrolyte provided by the present invention is a hydrophobically modified molecular sieve. The hydrophobic layer covered by the molecular sieve reduces the adsorption capacity of the molecular sieve to moisture, reduces the sensitivity of the composite solid electrolyte containing the modified molecular sieve to moisture in the air, and reduces the risk of pore blockage and side reactions of the composite solid electrolyte, thereby making the composite solid electrolyte have better electrochemical stability;
[0070] (2) The structure of the hydrophobically modified molecular sieve obtained after the molecular sieve is hydrophobically modified in the preparation method provided in the present invention remains unchanged, the modification method is simple and environmentally friendly, and the raw materials can be recycled, which is suitable for large-scale industrial production; in addition, the composite solid electrolyte prepared by the hydrophobically modified molecular sieve can greatly reduce the adsorption and reaction of moisture and oxygen in the air during the preparation of solid-state batteries and the operation of solid-state batteries, thereby making the solid-state battery have excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 This is the SEM image of the hydrophobically modified X molecular sieve prepared in Example 1.
[0072] Figure 2 This is an optical image of the composite solid electrolyte provided in Example 1.
[0073] Figure 3 This is a cross-sectional SEM image of the composite solid electrolyte provided in Example 1.
[0074] Figure 4 This is the electrochemical window curve of the composite solid electrolyte provided in Example 1.
[0075] Figure 5 This is the long cycle curve of the composite solid electrolyte provided in Example 1. DETAILED DESCRIPTION
[0076] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0077] Example 1
[0078] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, wherein the modified molecular sieve in the composite solid electrolyte is a hydrophobically modified X molecular sieve, and the hydrophobically modified X molecular sieve comprises an X molecular sieve and a hydrophobic layer covering the surface of the X molecular sieve;
[0079] The composite solid electrolyte also includes a molecular weight of 4×10 5 PVDF-HFP and LiTFSI.
[0080] The preparation method of the composite solid electrolyte comprises:
[0081] (1) calcining and activating the X molecular sieve at 400° C. for 4 h to obtain an activated X molecular sieve;
[0082] (2) mixing the activated X molecular sieve obtained in step (1), trimethylsilyl chloride, ethanol and ammonia water with a mass concentration of 20 wt % by magnetic stirring at a speed of 400 r / min, a temperature of 40° C., and a time of 8 h, to carry out a silanization reaction, and then washing with ethanol three times and vacuum drying at 80° C. for 12 h to obtain a hydrophobically modified X molecular sieve;
[0083] The solid-liquid ratio of the activated X molecular sieve to trimethylsilyl chloride in the mixture is 1:2, the solid-liquid ratio of the activated X molecular sieve to ethanol is 1:30, and the solid-liquid ratio of the activated X molecular sieve to ammonia water is 1:1. The units of the solid-liquid ratios are g / mL, and the mass fraction of the ammonia water is 30%;
[0084] (3) PVDF-HFP, LiTFSI, DMF and the hydrophobically modified X molecular sieve obtained in step (2) are mixed to obtain a mixed slurry, wherein the mixture is stirred at 400 r / min at 45° C. for 24 hours, and the mass ratio of PVDF-HFP, LiTFSI, the obtained hydrophobically modified X molecular sieve and DMF in the mixture is 1.2:1:0.15:4. The obtained mixed slurry is injected into a mold for molding, and then vacuum dried at 60° C. for 24 hours to obtain the composite solid electrolyte.
[0085] Example 2
[0086] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, wherein the modified molecular sieve in the composite solid electrolyte is a hydrophobically modified TS-1 molecular sieve, and the hydrophobically modified TS-1 molecular sieve comprises a TS-1 molecular sieve and a hydrophobic layer covering the surface of the TS-1 molecular sieve;
[0087] The composite solid electrolyte also includes a molecular weight of 5×10 5 PVDF-HFP and LiTFSI.
[0088] The preparation method of the composite solid electrolyte comprises:
[0089] (1) calcining and activating the TS-1 molecular sieve at 500° C. for 2 h to obtain an activated TS-1 molecular sieve;
[0090] (2) mixing the activated TS-1 molecular sieve obtained in step (1), dimethyldiethoxysilane, ethanol and a sodium hydroxide aqueous solution with a mass concentration of 5 wt % by magnetic stirring at a speed of 450 r / min, a temperature of 35° C., and a time of 24 h, to carry out a silanization reaction, then washing with ethanol three times and vacuum drying at 60° C. for 12 h to obtain a hydrophobically modified TS-1 molecular sieve;
[0091] The solid-liquid ratio of the activated TS-1 molecular sieve to dimethyldiethoxysilane in the mixture is 1:1, the solid-liquid ratio of the activated TS-1 molecular sieve to ethanol is 1:30, and the solid-liquid ratio of the activated TS-1 molecular sieve to sodium hydroxide-water solution is 1:0.8, the units of the solid-liquid ratios are all g / mL, and the mass fraction of the sodium hydroxide-water solution is 15%;
[0092] (3) PVDF-HFP, LiTFSI, NMP and the hydrophobically modified TS-1 molecular sieve obtained in step (2) are mixed to obtain a mixed slurry, wherein the mixture is stirred at a speed of 450 r / min at 35° C. for 18 hours, and the mass ratio of PVDF-HFP, LiTFSI, the obtained hydrophobically modified TS-1 molecular sieve and NMP in the mixture is 1.5:1:0.1:8. The obtained mixed slurry is injected into a mold for molding, and then vacuum dried at 65° C. for 18 hours to obtain the composite solid electrolyte.
[0093] Example 3
[0094] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, wherein the modified molecular sieve in the composite solid electrolyte is a hydrophobically modified MCM-22 molecular sieve, wherein the hydrophobically modified MCM-22 molecular sieve comprises an MCM-22 molecular sieve and a hydrophobic layer covering the surface of the MCM-22 molecular sieve;
[0095] The composite solid electrolyte also includes a molecular weight of 4.5×10 5 PVDF-HFP and LiTFSI.
[0096] The preparation method of the composite solid electrolyte comprises:
[0097] (1) calcining and activating the MCM-22 molecular sieve at 300° C. for 6 h to obtain an activated MCM-22 molecular sieve;
[0098] (2) mixing the activated MCM-22 molecular sieve obtained in step (1), dimethyldiethoxysilane, ethanol and an aqueous solution of ammonium carbonate having a mass concentration of 40 wt % by magnetic stirring at a speed of 500 r / min, a temperature of 40° C., and a time of 16 h, to carry out a silanization reaction, and then washing with ethanol 5 times and vacuum drying at 60° C. for 12 h to obtain a hydrophobically modified MCM-22 molecular sieve;
[0099] The solid-liquid ratio of the activated MCM-22 molecular sieve to dimethyldiethoxysilane in the mixture is 1:0.5, the solid-liquid ratio of the activated MCM-22 molecular sieve to ethanol is 1:15, and the solid-liquid ratio of the activated X molecular sieve to ammonium carbonate-water solution is 1:0.2, the units of the solid-liquid ratios are g / mL, and the mass fraction of the ammonium carbonate-water solution is 35%;
[0100] (3) PVDF-HFP, LiTFSI, tetrahydrofuran and the hydrophobically modified MCM-22 molecular sieve obtained in step (2) are mixed to obtain a mixed slurry, wherein the mixture is stirred at a speed of 500 r / min at 35° C. for 12 hours, and the mass ratio of PVDF-HFP, LiTFSI, the obtained hydrophobically modified MCM-22 molecular sieve and tetrahydrofuran in the mixture is 0.5:1:1.2:3. The obtained mixed slurry is injected into a mold for molding, and then vacuum dried at 70° C. for 12 hours to obtain the composite solid electrolyte.
[0101] Example 4
[0102] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, wherein the modified molecular sieve in the composite solid electrolyte is a hydrophobically modified Y molecular sieve, wherein the hydrophobically modified Y molecular sieve comprises a Y molecular sieve and a hydrophobic layer covering the surface of the Y molecular sieve;
[0103] The composite solid electrolyte also includes a molecular weight of 5×10 5 PVDF-HFP and LiTFSI.
[0104] The preparation method of the composite solid electrolyte comprises:
[0105] (1) calcining and activating the Y molecular sieve at 300-600° C. for 2-8 hours to obtain an activated Y molecular sieve;
[0106] (2) mixing the activated molecular sieve obtained in step (1), dimethyldiethoxysilane, ethanol and ammonia water with a mass concentration of 20 wt % by magnetic stirring at a speed of 450 r / min, a temperature of 35° C., and a time of 4 h, to carry out a silanization reaction, then washing with ethanol 4 times and vacuum drying at 50° C. for 4 h to obtain a hydrophobically modified Y molecular sieve;
[0107] The solid-liquid ratio of the activated Y molecular sieve to dimethyldiethoxysilane in the mixture is 1:0.1, the solid-liquid ratio of the activated molecular sieve to the reaction solvent is 1:35, and the solid-liquid ratio of the activated molecular sieve to ammonia water is 1:0.1. The units of the solid-liquid ratios are all g / mL, and the mass fraction of the ammonia water is 28%;
[0108] (3) PVDF-HFP, LiTFSI, anhydrous acetonitrile and the hydrophobically modified Y molecular sieve obtained in step (2) are mixed to obtain a mixed slurry, wherein the mixture is stirred at a speed of 400 r / min at 40° C. for 18 hours, and the mass ratio of PVDF-HFP, LiTFSI, the obtained hydrophobically modified Y molecular sieve and anhydrous acetonitrile in the mixture is 0.8:1:1:3. The obtained mixed slurry is injected into a mold for molding, and then vacuum dried at 60° C. for 8 hours to obtain the composite solid electrolyte.
[0109] Example 5
[0110] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, wherein the modified molecular sieve in the composite solid electrolyte is a hydrophobically modified MCM-22 molecular sieve, wherein the hydrophobically modified MCM-22 molecular sieve comprises an MCM-22 molecular sieve and a hydrophobic layer covering the surface of the MCM-22 molecular sieve;
[0111] The composite solid electrolyte also includes a molecular weight of 4.5×10 5 PVDF-HFP and LiTFSI.
[0112] The preparation method of the composite solid electrolyte comprises:
[0113] (1) calcining and activating the MCM-22 molecular sieve at 450° C. for 3 h to obtain an activated MCM-22 molecular sieve;
[0114] (2) mixing the activated MCM-22 molecular sieve obtained in step (1), dodecyltrimethoxysilane, ethanol and a sodium hydroxide aqueous solution with a mass concentration of 10 wt % by magnetic stirring at a speed of 500 r / min, a temperature of 45° C., and a time of 10 h, to carry out a silanization reaction, then washing with ethanol three times and vacuum drying at 100° C. for 2 h to obtain a hydrophobically modified MCM-22 molecular sieve;
[0115] The solid-liquid ratio of the activated MCM-22 molecular sieve to dodecyltrimethoxysilane in the mixture is 1:1.5, the solid-liquid ratio of the activated molecular sieve to ethanol is 1:35, and the solid-liquid ratio of the activated MCM-22 molecular sieve to sodium hydroxide-water solution is 1:4, the units of the solid-liquid ratios are g / mL, and the mass fraction of the sodium hydroxide-water solution is 10%;
[0116] (3) PVDF-HFP, LiTFSI, DMSO and the hydrophobically modified MCM-22 molecular sieve obtained in step (2) are mixed to obtain a mixed slurry, wherein the mixture is stirred at a speed of 350 r / min at 50° C. for 24 hours, and the mass ratio of PVDF-HFP, LiTFSI, the obtained hydrophobically modified MCM-22 molecular sieve and DMSO in the mixture is 1.4:1:0.08:10. The obtained mixed slurry is injected into a mold for molding, and then vacuum dried at 90° C. for 16 hours to obtain the composite solid electrolyte.
[0117] Example 6
[0118] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, which is the same as that of Embodiment 1 except that PVDF-HFP is replaced by a PAN-type solid electrolyte of equal mass.
[0119] Example 7
[0120] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, which is the same as that of Embodiment 1 except that PVDF-HFP is replaced by polyvinylidene fluoride of the same mass.
[0121] Example 8
[0122] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, except that the molecular weight of the PVDF-HFP is 3×10 5 Except for this, the rest are the same as in Example 1.
[0123] Example 9
[0124] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, except that the molecular weight of the PVDF-HFP is 6×10 5 Except for this, the rest are the same as in Example 1.
[0125] Example 10
[0126] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, which is the same as Embodiment 1 except that step (1) of the preparation method of the composite solid electrolyte is omitted.
[0127] Embodiment 11
[0128] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, which is the same as that of Embodiment 1 except that in step (2) of the method for preparing the composite solid electrolyte, the solid-liquid ratio of the activated X molecular sieve to trimethylsilyl chloride is 1:0.02.
[0129] Example 12
[0130] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, which is the same as that of Embodiment 1 except that in step (2) of the method for preparing the composite solid electrolyte, the solid-liquid ratio of the activated X molecular sieve to trimethylsilyl chloride is 1:7.
[0131] Example 13
[0132] This embodiment provides a composite solid electrolyte comprising a modified molecular sieve, which is the same as Embodiment 1 except that the mixing of ammonia water in step (2) of the preparation method of the composite solid electrolyte is omitted.
[0133] Comparative Example 1
[0134] This comparative example provides a composite solid electrolyte containing molecular sieves, which is the same as Example 1 except that the hydrophobically modified X molecular sieve is replaced with an X molecular sieve of the same mass.
[0135] The hydrophobically modified X molecular sieve prepared in Example 1 was tested using a scanning electron microscope, and the SEM image of the hydrophobically modified X molecular sieve was obtained as shown in FIG. Figure 1 As shown;
[0136] The composite solid electrolyte provided in Example 1 was tested using an optical microscope to obtain an optical image of the composite solid electrolyte. Figure 2 As shown;
[0137] The composite solid electrolyte provided in Example 1 was tested using a scanning electron microscope, and a cross-sectional SEM image of the composite solid electrolyte was obtained as shown in FIG. Figure 3 As shown;
[0138] Depend on Figure 1 , Figure 2 and Figure 3 It can be obtained that the composite solid electrolyte membrane is colorless and transparent, and has a thickness of about 60 μm.
[0139] The composite solid electrolytes provided in the above embodiments and comparative examples were subjected to electrochemical window tests. The electrochemical window test method was as follows: linear cyclic voltammetry was used for testing. The electrochemical window of the composite solid electrolyte obtained by the test was shown in Table 1. Among them, the electrochemical window curve of the composite solid electrolyte provided in Example 1 is shown in Table 1. Figure 4 As shown;
[0140] The composite solid electrolyte provided in the above embodiment and comparative example was matched with a 622-type nickel-cobalt-manganese positive electrode sheet and a lithium metal negative electrode sheet to prepare a solid-state lithium metal battery; the obtained solid-state lithium metal battery was subjected to a cycle performance test, and the capacity retention rate and coulombic efficiency after 100 cycles at 0.2C current at 25°C were shown in Table 1; wherein, the long cycle curve of the composite solid electrolyte provided in Example 1 is shown in Figure 5shown.
[0141] Table 1
[0142]
[0143]
[0144] From Table 1, we can get:
[0145] (1) The composite solid electrolytes comprising modified molecular sieves provided in Examples 1 to 5 have a wide electrochemical window, and the solid-state battery prepared using the composite solid-state electrolyte has a high capacity retention rate and coulombic efficiency after 100 cycles, that is, the obtained solid-state battery has excellent electrochemical stability;
[0146] (2) By comparing Example 1 with Examples 6 and 7, it can be seen that the solid electrolyte in the present invention is preferably PVDF-HFP, which has excellent oxidation resistance and lithium stability, and is used in solid-state batteries to further enhance the stability of solid-state batteries;
[0147] (3) By comparing Example 1 with Examples 8 and 9, it can be seen that the molecular weight of PVDF-HFP in the present invention affects the performance of the obtained solid-state battery; when the molecular weight of PVDF-HFP is between 4×10 5 ~5×10 5 When the molecular weight of PVDF-HFP is within the range of , PVDF-HFP can provide sufficient mechanical strength and flexibility while maintaining high ionic conductivity. In addition, PVDF-HFP with a molecular weight within this range helps to improve the thermal stability of the electrolyte, which is crucial to improving the safety and cycle stability of solid-state batteries.
[0148] (4) By comparing Example 1 with Example 10, it can be seen that the calcination activation before the hydrophobic modification in the preparation method of the composite solid electrolyte of the present invention can remove the moisture and impurities adsorbed in the molecular sieve, thereby preventing the moisture and impurities from having an adverse effect on the performance of the hydrophobically modified molecular sieve, thereby facilitating the improvement of the cycle stability of the obtained solid-state battery;
[0149] (5) By comparing Example 1 with Examples 11 and 12, it can be seen that the solid-liquid ratio of the molecular sieve to the silanization agent in the preparation method of the composite solid electrolyte of the present invention affects the performance of the obtained solid-state battery; when the solid-liquid ratio of the molecular sieve to the silanization agent is 1: (0.1-5), it is beneficial to form a hydrophobic layer of appropriate thickness without affecting the structure of the molecular sieve, and enhance the hydrophobicity of the molecular sieve without affecting the performance of the molecular sieve, thereby improving the stability of the solid-state battery;
[0150] (6) By comparing Example 1 with Example 13, it can be seen that the catalyst is added to the preparation method of the composite solid electrolyte of the present invention, which promotes the hydrolysis reaction of the silanization agent, is conducive to the uniform grafting of the hydrophobic group on the surface of the molecular sieve, and thus improves the stability of the solid-state battery;
[0151] (7) By comparing Example 1 with Comparative Example 1, it can be seen that the modified molecular sieve in the composite solid electrolyte provided by the present invention is a hydrophobically modified molecular sieve, and the hydrophobic layer covered by the molecular sieve reduces the adsorption capacity of the molecular sieve to moisture, reduces the sensitivity of the composite solid electrolyte containing the modified molecular sieve to moisture in the air, and reduces the risk of pore blockage and side reactions of the composite solid electrolyte, thereby making the composite solid electrolyte have better electrochemical stability; the structure of the hydrophobically modified molecular sieve obtained after the molecular sieve is hydrophobically modified in the preparation method provided by the present invention does not change, the modification method is simple and environmentally friendly, and the raw materials can be reused, which is suitable for large-scale industrial production; in addition, the composite solid electrolyte prepared with the hydrophobically modified molecular sieve can greatly reduce the adsorption and reaction of moisture and oxygen in the air during the preparation of solid-state batteries and the operation of solid-state batteries, thereby making the solid-state battery have excellent cycle stability.
[0152] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A composite solid electrolyte comprising a modified molecular sieve, characterized in that: The modified molecular sieve in the composite solid electrolyte is a hydrophobically modified molecular sieve, and the hydrophobically modified molecular sieve comprises a molecular sieve and a hydrophobic layer covering the surface of the molecular sieve.
2. The composite solid electrolyte according to claim 1, characterized in that The composite solid electrolyte also includes a solid electrolyte and a lithium salt. The solid electrolyte includes PVDF-HFP. The molecular weight of the PVDF-HFP is 4×10 5 ~5×10 5 .
3. A method for preparing the composite solid electrolyte according to claim 1 or 2, characterized in that: The preparation method comprises: The molecular sieve is hydrophobically modified to form a hydrophobic layer on the surface of the molecular sieve to obtain a hydrophobically modified molecular sieve; and the obtained hydrophobically modified molecular sieve is used as a raw material to prepare a composite solid electrolyte.
4. The preparation method according to claim 3, characterized in that: The preparation method further comprises calcination activation before the hydrophobic modification, wherein the calcination activation temperature is 300 to 600° C. and the time is 2 to 8 hours.
5. The preparation method according to claim 3, characterized in that: The hydrophobic modification method comprises: mixing a molecular sieve, a silanization agent, a reaction solvent and a catalyst, and performing a silanization reaction to obtain a hydrophobically modified molecular sieve; The solid-liquid ratio of the molecular sieve to the silanization agent in the mixture is 1:(0.1-5), the solid-liquid ratio of the molecular sieve to the reaction solvent is 1:(5-40), and the solid-liquid ratio of the molecular sieve to the catalyst is 1:(0.1-5), and the units of the solid-liquid ratios are all g / mL.
6. The preparation method according to claim 5, characterized in that: The catalyst comprises any one of sodium hydroxide aqueous solution, ammonium carbonate aqueous solution or ammonia water or a combination of at least two thereof, and the mass concentration of the solute in the catalyst is 5-40wt%.
7. The preparation method according to claim 3, characterized in that: The method for preparing a composite solid electrolyte using the obtained hydrophobically modified molecular sieve as a raw material comprises: The solid electrolyte, lithium salt, organic solvent and the obtained hydrophobically modified molecular sieve are mixed to obtain a mixed slurry, the obtained mixed slurry is cast into a shape, and then vacuum dried to obtain the composite solid electrolyte; The mass ratio of the solid electrolyte, the lithium salt and the obtained hydrophobically modified molecular sieve in the mixture is (0.3-1.5):1:(0.05-1.5).
8. The preparation method according to claim 3, characterized in that: The preparation method comprises: (1) calcining and activating the molecular sieve at 300-600° C. for 2-8 hours to obtain an activated molecular sieve; (2) mixing the activated molecular sieve obtained in step (1), a silanization agent, a reaction solvent and a catalyst having a solute mass concentration of 5 to 40 wt % by magnetic stirring at a speed of 150 to 600 r / min, a temperature of 25 to 60° C., and a time of 2 to 48 h, performing a silanization reaction, and then washing with ethanol 3 to 5 times and vacuum drying at 30 to 100° C. for 1 to 24 h to obtain a hydrophobically modified molecular sieve; The solid-liquid ratio of the activated molecular sieve to the silanization agent in the mixture is 1:(0.1-5), the solid-liquid ratio of the activated molecular sieve to the reaction solvent is 1:(5-40), and the solid-liquid ratio of the activated molecular sieve to the catalyst is 1:(0.1-5), and the units of the solid-liquid ratios are all g / mL; (3) A solid electrolyte, a lithium salt, an organic solvent and the hydrophobically modified molecular sieve obtained in step (2) are mixed to obtain a mixed slurry, wherein the mass ratio of the solid electrolyte, the lithium salt and the hydrophobically modified molecular sieve in the mixture is (0.3-1.5):1:(0.05-1.5), and the mass ratio of the lithium salt to the organic solvent is 1:(2-12). The obtained mixed slurry is injected into a mold for molding, and then vacuum dried at 60-120° C. for 8-24 hours to obtain the composite solid electrolyte.
9. A solid-state battery, characterized in that: The solid-state battery comprises the composite solid-state electrolyte according to claim 1 or 2.
10. A vehicle, characterized in that: The vehicle includes the solid-state battery of claim 9.
Citation Information
Patent Citations
Molecular sieve based solid electrolyte and preparation method thereof, and integrated solid electrolyte-electrode material
CN112864456A
Modified molecular sieve-based solid electrolyte as well as preparation method and application thereof
CN117039129A
Ionic liquid-loaded mesoporous molecular sieve as well as preparation method and application thereof
CN112076726A
Hydrophobic modified molecular sieve as well as preparation method and application thereof
CN114570328A
Modifide mesopore molecular sieve composite full solid state polymer electrolyte and its preparation method
CN1903940A
Cited By
Solid electrolyte precursor, solid electrolyte and preparation method thereof
CN120809957A